Frequency of antibiotic resistant enteropathogenic Escherichia coli (EPEC) in bovine carcasses at a slaughterhouse in Brazil (Research, Society and Development, 2020)
Escherichia coli (E. coli) comes in second place among microorganisms involved in outbreaks of foodborne diseases in Brazil and is among the 4 most prominent worldwide. Due to its importance, the purpose of this work is to verify microbiological quality by the presence of E. coli in bovine carcasses. A total of 365 E. coli were isolated by swabs of 154 carcasses of cattle, slaughtered in the municipality of Mineiros – GO, Brazil. The frequency of E. coli in the samples collected was 81% (125/154). Of these E. coli, 16 had the gene eae, and none presented the genes stx1 or stx2, so were therefore classified as EPEC. Thus, the frequency of EPEC in the carcasses was 9.7% (15/154). The strains were classified as part of the A or B1 groups. As for antimicrobial resistance, the antibiotics with the highest percentages of resistance were Cephalothin with 82% (41/50), followed by Gentamicin and Amikacin with 26% (13/50) each. None of the samples showed any production of the extended-spectrum beta-lactamase enzyme, but three EPECs were classified as multi-drug resistant. The results demonstrate the presence of multi-resistant EPEC in bovine carcasses slaughtered in Mineiros city, Brazil.